2006
DOI: 10.1089/scd.2006.15.391
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem-like Cell Line Derived from a Nonhematopoietic Population of Human Umbilical Cord Blood

Abstract: The ability of stem and progenitor cells to proliferate and differentiate into other lineages is widely viewed as a characteristic of stem cells. Previously, we have reported that cells from a CD34(-) (nonhematopoietic) adherent subpopulation of human cord blood can acquire a feature of multipotential neural progenitors in vitro. In the present study, using these cord blood-derived stem cells, we have established a clonal cell line termed HUCB-NSCs (human umbilical cord blood-neural stem cells) that expresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 64 publications
1
73
0
1
Order By: Relevance
“…These cells could potentially be included in our cell culture since we do not remove the non-hematopoietic cells. Since the number of CD45+ cells was reduced in our long-term culture, this suggests that our long-term culture could be transforming into the neural stemlike line detected by Buzanska et al [3].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These cells could potentially be included in our cell culture since we do not remove the non-hematopoietic cells. Since the number of CD45+ cells was reduced in our long-term culture, this suggests that our long-term culture could be transforming into the neural stemlike line detected by Buzanska et al [3].…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies demonstrate that long-term culture of HUCB enhanced neural content of cell cultures (Jurga et al [24]; an observation which we also see), however, Jain et al [21] saw an overall decrease in neuronal number with long-term culture, but an increased migration of cells with a neuronal phenotype (but not of total cells) in the hippocampus in intact rat brain. Buzanska et al [3] have also generated a neural stem-like line from the non-hematopoietic fraction of HUCB. These cells could potentially be included in our cell culture since we do not remove the non-hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68][69][70] Cell lines with NSC properties have been established from HUCB following immune-depletion of the CD34-positive cells from CB and spontaneous aggregation and differentiation with stimulation by epithelial growth factor. 71 When such CB-NSCs were seeded on human-originated biodegradable scaffold, they were able to differentiate into neurons, form functional circuits and generate spontaneous field/action potentials. 72 Recently, Tracy et al 73 demonstrated that oligodendrocyte progenitors could also be isolated and expanded ex vivo from human CB.…”
Section: Cb Stem Cell Biologymentioning
confidence: 99%
“…HUCB has a good chance of becoming the ideal source for such standardized transplantable material. Our laboratory has successfully derived a non-immortalized cell-line with properties of neural stem cells (Buzanska et al, 2003;Buzanska et al, 2006b). This cell line of HUCB-NSCs serves as a useful prototype for the ideal transplantable material depicted above, and, upon sufficient characterization in animal models, it has a strong potential for clinical use.…”
Section: Why We Are Interested In Human Umbilical Cord Blood (Hucb) -mentioning
confidence: 99%
“…The first (Buzanska et al, 2001a) and then published in 2002 (Buzanska et al, 2002). Thereafter, through repeated passages of floating, round-shaped, nestin-positive and clonogenic cells from these neural progenitors population we have established the first, expanding, indefinitely growing HUCB-NSC cell line (Buzanska et al, 2003;Buzanska et al, 2006b). …”
Section: Historical Notementioning
confidence: 99%